ANALISIS KESALAHAN HITSUJUN KANJI PADA MAHASISWA SEMESTER III PRODI BAHASA JEPANG STBA CIPTO HADI PRANOTO - Cerli Dewi Utamani; Kliwon Sahudi (Jurnal SORA, 2021)
In teaching and learning activities there are writing errors made by Japanese language learners. Some errors are caused by bushu (a form of classification of kanji), kakusuu (number of lines or strokes), hitjujun (sequence of writing lines or strokes) which must be mastered by basic Japanese language learners, especially STBA student of Cipto Hadi Pranoto. This study aims to find out the errors in writing Kanji for Semester III students of STBA Cipto Hadi Pranoto. The method used in this research is a qualitative case study. The data was taken from the test given to the research sample and then analyzed for kanji writing errors based on the sequence of writing lines or strokes. The result of this study is the error rate of kanji writing that is not in the order of writing lines or strokes is 79%. Factors that cause errors include difficulty in memorizing kanji with a large number of strokes, many similar kanji but different reading and writing ways, almost the same form of bushu but different hitsujun, not paying attention to hitjujun kanji, and learning kanji without remembering hitsujun kanji.